Optimal problem of cost function for the linear neutral systems - Jong Yeoul Park; Yong Han Kang (International Journal of Mathematics and Mathematical Sciences)
We study the optimal control problem of a system governed by linear neutral type in Hilbert space X. We investigate optimal condition for quadratic cost function and as applications, we give some examples.